Socialization of the Natural Mangrove Crab Hatchery Technique in Baroh Village, Langsa Lama District, Aceh - Siti Komariyah; Siti Balqies Indra; Fauziah Azmi (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
Some of the people of Baroh Village work as fish cultivators, including milkfish, shrimp and crabs. For crab seeds themselves, crab cultivators in Baroh Village still depend on catches from nature. The dependence of crab cultivators on seeds from nature is caused by ignorance in conducting crab hatcheries, both natural and semi-artificial. In addition, there has been no socialization provided by the local fisheries service regarding crab hatchery. So the team provided a solution by providing socialization of natural crab hatchery to crab cultivators. The socialization of the mangrove crab hatchery technique was attended by the wives of the cultivators. The participants were very enthusiastic about participating in each activity, this was shown by the questions from the participants. From the results of the socialization, there were several problems for cultivators to carry out hatchery activities, such as the availability of adequate equipment and the availability of natural food as food for crab larvae that are difficult to culture.